2022
DOI: 10.21203/rs.3.rs-1370541/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased household transmission and immune escape of the SARS-CoV-2 Omicron variant compared to the Delta variant: evidence from Norwegian contact tracing and vaccination data

Abstract: Understanding the rapid epidemic growth of the novel SARS-CoV-2 Omicron variant is critical for public health management. We compared the secondary attack rate (SAR) of the Omicron and Delta variants in households using Norwegian contact tracing data from December 2021 to January 2022. Omicron SAR was higher (51%) than Delta (36%), with a relative risk (RR) of 1.41 (95% CI 1.27–1.56). We observed increased susceptibility to Omicron infection in household contacts compared to Delta independent of vaccination st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 1 publication
2
34
1
Order By: Relevance
“…We identified 2097 records (1791 from PubMed, 306 from medRxiv, and 2 from reference lists of eligible articles) published between June 18, 2021, and March 8, 2022 (eFigure 1 in the Supplement ). Fifty-eight new studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 (eTable 2 in the Supplement ) were combined with 77 studies from ou...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 2097 records (1791 from PubMed, 306 from medRxiv, and 2 from reference lists of eligible articles) published between June 18, 2021, and March 8, 2022 (eFigure 1 in the Supplement ). Fifty-eight new studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 (eTable 2 in the Supplement ) were combined with 77 studies from ou...…”
Section: Resultsmentioning
confidence: 99%
“…This reflects new variants and changing vaccination coverage. From highest to lowest, the overall household SARs were 42.7% (95% CI, 35.4%-50.4%) for Omicron (7 studies 55 , 61 , 62 , 63 , 64 , 67 , 68 ), 36.4% (95% CI, 33.4%-39.5%) for Alpha (11 studies 18 , 19 , 21 , 23 , 28 , 33 , 44 , 46 , 49 , 50 , 69 ), 29.7% (95% CI, 23.0%-37.3%) for Delta (16 studies 18 , 20 , 24 , 26 , 35 , 37 , 42 , 46 , 50 , 55 , 57 , 61 , 64 , 65 , 66 , 70 ), and 22.5% (95% CI, 18.6%-26.8%) for Beta (3 studies 15 , 18 , 50 ) ( Figure 2 ). High heterogeneity was found among studies for Omicron ( I 2 = 98.2%; P < .001) and Delta ( I 2 = 99.1%; P < .001), moderate for Alpha ( I 2 = 59.6%; P < .001), and low for Beta ( I 2 = 2.6%; P = .79).…”
Section: Resultsmentioning
confidence: 99%
“…Omicron is generally understood to have a transmission advantage but is less pathogenic than Delta, 16,17,36,37 however quantifying and thus comparing these parameters is difficult given differences in the populations in which they are circulating, and availability and access to early characterising data. While Omicron infections are dominating Delta infections in most parts of the world, its reproduction advantage may be due to increased inherent transmissibility, increased immunity escape, a different population response to arrival of Omicron, or some combination of these.…”
Section: Managing the Health Burdenmentioning
confidence: 99%
“…While Omicron infections are dominating Delta infections in most parts of the world, its reproduction advantage may be due to increased inherent transmissibility, increased immunity escape, a different population response to arrival of Omicron, or some combination of these. 37 To manage this uncertainty, we employed the calibration process described in the methods section. This exploited the availability of detailed Omicron epidemic data from two Australian states, Queensland and South Australia.…”
Section: Managing the Health Burdenmentioning
confidence: 99%
“…3 The immune escape capabilities are possibly conferred by K417N, 37 S477N, 38 E484A 38 and other novel mutations, while the binding affinity between RBD and hACE2 is retained due to strongly binding-improving mutations such as N501Y, 30,31 both contributing to the increased viral transmissibility of Omicron compared to earlier variants. [39][40][41] Early on during the pandemic, to gain a more complete view of the effect of RBD mutation, Starr et al 30 exhaustively assessed the impact of single amino acid changes on RBD expression and hACE2 binding. They found that 84.5% of the amino acid changes are detrimental, 7.5% are neutral and the rest 8.0% can lead to enhanced binding of the RBD with hACE2.…”
Section: Introductionmentioning
confidence: 99%